Stress impairs response to antidepressants by activating HPA axis and immune system. (September 2021) - Menke, A.; Nitschke, F.; Hellmuth, A.; Helmel, J.; Wurst, C.; Stonawski, S.; Blickle, M.; Weiß, C.; Weber, H.; Hommers, L.; Domschke, K.; Deckert, J.
Abstract : While early adverse events as well as severe stressful events occurring later in life have been associated with depression, the interaction is still not understood. The objective of this study is to disentangle the interaction by evaluating the main stress-response systems of the body, the hypothalamic-pituitary-adrenal (HPA-) axis and the immune system in depressed patients. HPA-axis function was evaluated by analyzing FKBP5, SGK1 and NR3C1 mRNA-expression in whole blood after an in vivo glucocorticoid receptor challenge with 1.5 mg dexamethasone in 150 depressed in-patients. Early adverse events were evaluated using the Childhood Trauma Questionnaire (CTQ), severe life events occurring one year prior to hospital admission were assessed with the List of Threatening Experiences (LTE). History of 3 and more severe life events was associated with a significantly impaired treatment response to antidepressants. Additionally, there was a significant association with an impaired GR-induction of SGK1 and FKBP5 mRNA expression, as well as with increased measures of the immune system such as lymphocyte count and CRP. These alterations were not observable in relation to early adverse effects. Severe life events that happen prior to the development of depression significantly impair the HPA-axis and the response to antidepressants. Therefore patients who report stressful life events should receive additional treatment options such as psychotherapy already at the beginning of therapy.